Laboratory Melting of Late-Winter Urban Snow Samples : The Magnitude and Dynamics of Releases of Heavy Metals and PAHs - Vijayan, Arya; Österlund, Helene; Marsalek, Jiri; Viklander, Maria (Water, Air, & Soil Pollution, 2019)
Laboratory snow melting experiments were conducted with actual late-winter snow samples, collected just before the final snowmelt, in two similar northern Swedish cities, Luleå and Umeå, to investigate releases of the selected heavy metals (HM) (Cu, Pb, Zn, and Cd) and 16 USEPA PAHs from melting snow. Metal concentrations were determined in three fractions: total, dissolved, and truly dissolved (defined as the fraction passing through a 3-kMWCO ultrafilter). Total HM concentrations in snowmelt were rather high at both sites and reflected the accumulation of pollutants in the roadside snowbanks over a period of about 5 months: Cd = 0.43, Cu = 303, Pb = 41.9, Zn = 817 (μg/l), and TSS = 2000 (mg/l) in Luleå samples and Cd = 1.87, Cu = 905, Pb = 165, Zn = 3150 (μg/l), and TSS = 4800 (mg/l) in Umeå samples. The difference between metal and TSS concentrations at the two sites of similar characteristics was attributed to a smaller volume snowbank in Umeå. The dissolved HM concentrations represented relatively small fractions of the total concentrations (0.3–6.9% in Luleå and 0.01–3.1% in Umeå). The truly dissolved fraction represented 71–90% of the dissolved fraction in Luleå and 74–98% in Umeå. At both sites, the dissolved fractions exhibited preferential elution from the laboratory snow piles. The PAHs studied (16 US EPA PAHs) were mostly particulate bound, with only 5–12% of the total burden contributed by the meltwater, and most dissolved concentrations below the reporting limits. PAH concentrations in the Luleå samples were about one-third to one-fourth of those in Umeå. In general, the releases of PAHs from the snowbank were delayed, compared with releases of meltwater, and showed similar release patterns as TSS. Validerad;2019;Nivå 2;2019-08-20 (johcin)